An Inconvenient Apocalpse, Environmental Collapse, Climate Crisis, and the Fate of Humanity - Keller, Harold W. (Journal of the Botanical Research Institute of Texas, 2023)
The evolutionary history of humans, known by the scientific name Homo sapiens (wise man), is the last living representative of a long fossil lineage of human-like populations. This book explores the wisdom of the current human populations, whose eight billion plus population growth and spread dominates present-day earth, and the possibility that these sheer numbers if left unchecked without the right choices, may sooner or later, destroy planet earth and perhaps go extinct. This book explores the questions posing human survival. Therefore, if you care about the survival of the most recent human species, you must read this book and consider the options that confront the future of our existence. Many other life forms that make up living components of ecosystems have gone extinct, and/or have merged with other extant species, so will human evolution follow the same time course?